Effect of HMGB1 on the Paracrine Action of EPC Promotes Post‐Ischemic Neovascularization in Mice. (October 2014) - Chen, Chao; Lin, Xiaojie; Wang, Jixian; Tang, Guanghui; Mu, Zhihao; Chen, Xiaoyan; Xu, Jin; Wang, Yongting; Zhang, Zhijun; Yang, Guo‐Yuan
Abstract Transplantation of endothelial progenitor cells (EPCs) leads to better outcomes in experimental stroke, but the mechanism remains unclear. It was reported that astrocytic‐high mobility group box1 (HMGB1) promoted endogenous EPC‐mediated neurovascular remodeling during stroke recovery. It is unclear whether HMGB1 involves in exogenous EPC‐mediated stroke recovery. In this study, we aim to explore whether microglial HMGB1 contributes to human peripheral blood‐derived (hPB)‐EPCs‐mediated neurovascular remodeling by modulating the paracrine function of exogenous hPB‐EPCs. Coculturing hPB‐EPCs with lipopolysaccharides stimulated BV2 cells upregulated Interleukin‐8 expression in hPB‐EPCs; this was blocked by treating BV2 cells with HMGB1 inhibitor Glycyrrhizin. Conditioned medium (CM) of hPB‐EPCs cocultured with BV2 cells promoted the viability and tube formation of human umbilical cord vein cells. Inhibiting either HMGB1 or IL‐8 could block the effect of hPB‐EPCs CM. In vivo study showed hPB‐EPCs transplantation improved neurobehavioral outcomes, reduced brain atrophy volume, and enhanced neovascularization in transient middle cerebral artery occlusion (tMCAO) mice. Intraperitoneally administration of HMGB1 inhibitor glycyrrhizin blocked the beneficial effect of hPB‐EPC transplantation. We did not observe the integration of green fluorescent protein‐labeled hPB‐EPCs with microvessels in peri‐infarct areas at day‐14 after tMCAO. In summary, the result suggested that HMGB1 upregulation in postischemic brain could promote exogenous hPB‐EPC‐mediated stroke recovery by modulating paracrine function of hPB‐EPCs. Stem Cells2014;32:2679–2689